Sandwich structure composite material, preparation method and application thereof, and supercapacitor

Through sandwich structure design, laser-induced graphene is combined with pseudocapacitive materials to form an integrated composite electrode material, which solves the problems of low energy density, poor cycle stability and low ion transfer efficiency of supercapacitor electrode materials, and achieves high specific capacitance and excellent cycle stability.

CN120709079APending Publication Date: 2025-09-26ANHUI GLANCO NEW MATERIAL TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510834486.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-20
Publication Date
2025-09-26

AI Technical Summary

Technical Problem

Existing supercapacitor electrode materials have problems such as low energy density, poor cycle stability and low ion transfer efficiency. Traditional three-dimensional graphene electrode materials still need to be improved in terms of ion transfer efficiency and pseudocapacitive activity.

Method used

A sandwich structure design is adopted to combine laser-induced graphene (LIPG) with pseudocapacitive materials to form a first LIPG layer, a LIPG@pseudocapacitive material composite layer and a second LIPG layer, which are connected by covalent bonds to form an integrated sandwich structure. The LIPG layer serves as the outer skeleton and the LIPG@pseudocapacitive material layer serves as the middle active layer.

Benefits of technology

It significantly improves the specific capacitance and cycle stability of the electrode, enhances the electrochemical performance, provides an efficient channel for ion transport through the porous structure, improves the mechanical strength, prevents the active material from falling off, and extends the electrode life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120709079A_ABST
    Figure CN120709079A_ABST
Patent Text Reader

Abstract

The invention discloses a sandwich structure composite material, a preparation method and application thereof and a supercapacitor, and relates to the technical field of electrode materials, the sandwich structure composite material comprises a first LIPG layer, an LIPG and pseudocapacitance material composite layer and a second LIPG layer, and the LIPG and pseudocapacitance material composite layer is arranged between the first LIPG layer and the second LIPG layer; according to the invention, the LIPG and the pseudocapacitance material are combined, and the obtained composite electrode material can be applied to a supercapacitor through the sandwich structure design, so that the electrochemical performance is improved, and the service life of the electrode is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrode materials, and in particular to a sandwich structure composite material, a preparation method and application thereof, and a supercapacitor. Background Art

[0002] With the continuous growth of energy demand and environmental pollution problems, supercapacitors, as a green and efficient energy storage device, have attracted much attention due to their excellent power density and fast charging and discharging capabilities. However, existing supercapacitor electrode materials have the following problems:

[0003] (1) Low energy density. Traditional electrode materials (such as single graphene electrodes) mainly rely on double-layer capacitance, which has low specific capacitance and is difficult to meet the high energy density requirements of high-performance supercapacitors.

[0004] (2) Poor cycle stability. The active materials of some composite electrode materials are easily detached or dissolved during long-term charge and discharge, resulting in a rapid decline in capacitance performance.

[0005] (3) Low ion transmission efficiency. The unreasonable structural design of the electrode material leads to a long ion transmission path and high resistance, which affects the charge and discharge rate and efficiency of the electrode.

[0006] Although traditional three-dimensional graphene electrode materials have good conductivity, their ion transport efficiency and pseudocapacitive activity still need to be improved. Therefore, the development of high-performance supercapacitor electrode materials is of great significance. Summary of the Invention

[0007] The technical problem to be solved by the present invention is to provide a composite material and a preparation method thereof, combining laser-induced graphene (LIPG) with a pseudocapacitive material, and through a sandwich structure design, making the resulting composite electrode material applicable to supercapacitors, thereby improving electrochemical performance and extending electrode life.

[0008] The technical problem to be solved by the present invention is achieved by adopting the following technical solutions:

[0009] A first object of the present invention is to provide a sandwich structure composite material, comprising a first LIPG layer, a LIPG@pseudocapacitive material composite layer and a second LIPG layer, wherein the LIPG@pseudocapacitive material composite layer is arranged between the first LIPG layer and the second LIPG layer.

[0010] In the present invention, the first LIPG layer and the second LIPG layer serve as the outer skeleton of the electrode, providing electron transmission channels and mechanical support; the LIPG@pseudocapacitor material composite layer serves as the middle active layer of the electrode, providing pseudocapacitor active sites; the three-layer structure is connected by covalent bonds to form an integrated sandwich structure.

[0011] Furthermore, the pseudocapacitive material is a transition metal oxide, including but not limited to one or more of manganese oxide, iron oxide, cobalt oxide, and nickel oxide.

[0012] As a specific embodiment, the pseudocapacitive material is a heterostructure of Mn3O4 and MnO2.

[0013] Furthermore, the thickness of the first LIPG layer and the second LIPG layer are both 150-200 μm; the pore size distribution of the first LIPG layer and the second LIPG layer is small mesopores of 2-5 nm.

[0014] Furthermore, the thickness of the LIPG@pseudocapacitor material layer is 200-300 μm; the pore size distribution of the LIPG@pseudocapacitor material layer is macromesopores of 5-50 nm.

[0015] Furthermore, the specific surface area of ​​the first LIPG layer and the second LIPG layer is 500-600 m2 / g, and the electrical conductivity is 800-1000 S / m.

[0016] Furthermore, the mass proportion of the pseudocapacitive material in the LIPG@pseudocapacitive material layer is 10-20%.

[0017] A second object of the present invention is to provide a method for preparing a sandwich structure composite material, comprising the following steps:

[0018] (1) forming a carbon precursor into a thin film and irradiating it with a laser to form a first LIPG layer;

[0019] (2) uniformly coating a mixed solution of a carbon precursor and a pseudocapacitive material precursor on the surface of the first LIPG layer, and irradiating the layer with a laser to form a LIPG@pseudocapacitive material composite layer on the first LIPG layer;

[0020] (3) A carbon precursor solution is uniformly coated on the surface of the LIPG@pseudocapacitor material composite layer, and laser irradiation is performed to form a second LIPG layer on the LIPG@pseudocapacitor material composite layer to obtain a sandwich structure composite electrode material.

[0021] Furthermore, the carbon precursor includes but is not limited to one or more of polymer, lignin, cellulose, activated carbon, biomass carbon, graphite, coke, and pyrolytic carbon.

[0022] Furthermore, the pseudocapacitive material precursor is a transition metal salt, including but not limited to one or more of manganese acetate, iron acetate, nickel acetate, and cobalt acetate.

[0023] Furthermore, the carbon precursor is formed into a thin film using a solution film formation method. Specifically, the carbon precursor solution is formed into a film on a substrate, and after the sandwich structure composite electrode material is finally obtained, the substrate is peeled off. The substrate is made of one or more of polymer, metal, carbon, and carbon fiber; the substrate is in the form of one or more of film, powder, fiber, paper, cloth, and foam.

[0024] Furthermore, the mass ratio of the carbon precursor to the pseudocapacitive material precursor in the mixed solution is 1.5-2.5:1.

[0025] Furthermore, the laser is one or more of solid laser, liquid laser, gas laser, semiconductor laser, fiber laser, pulse laser, and continuous wave laser.

[0026] Furthermore, the laser wavelength of the laser irradiation is 1 to 1000 μm, the laser power is 0.1 to 100 W, the scanning rate is 1 to 2000 mm / s, and the spot size is 10 -9 ~10 2 m, scanning spacing is 0.01~5mm, pulse frequency is 1~100kHz, focal length is 1~200cm, and voltage is 0.01~1000kV.

[0027] Furthermore, an annealing treatment is added before laser irradiation of the first LIPG layer coated with a mixed solution of a carbon precursor and a pseudocapacitive material precursor, and the LIPG@pseudocapacitive material composite layer coated with the carbon precursor solution. The annealing treatment is performed at a temperature of 60-80°C for 0.8-1 hour. This annealing treatment removes excess solvent and forms a uniform thin film.

[0028] The third object of the present invention is to provide application of the sandwich structure composite material in supercapacitors.

[0029] A fourth object of the present invention is to provide a supercapacitor using the sandwich structure composite material as a positive electrode and / or a negative electrode.

[0030] Depending on the type of transition metal oxide used in the pseudocapacitive material, the resulting sandwich composite can be used as the positive and negative electrodes of a supercapacitor. When the pseudocapacitive material is manganese oxide, cobalt oxide, or nickel oxide, the sandwich composite can serve as the positive electrode; when the pseudocapacitive material is iron oxide, the sandwich composite can serve as the negative electrode.

[0031] A fifth object of the present invention is to provide an asymmetric supercapacitor using the sandwich structure composite material as a positive electrode.

[0032] Furthermore, the potential window of the asymmetric supercapacitor is 0-1.6V, and the energy density is 190-200μWh·cm - 2. Power density is 500-600 μW·cm - 2. The capacitance retention rate is greater than 90% after 10,000 cycles.

[0033] The beneficial effects of the present invention are:

[0034] 1. The present invention adopts a sandwich structure design, utilizes the high conductivity and porosity of the LIPG layer and the pseudocapacitive activity of the pseudocapacitive material, and significantly improves the specific capacitance and cycle stability of the electrode.

[0035] 2. The present invention provides efficient channels for ion transport through the design of small and large mesopores in the sandwich structure, thereby enhancing the electrochemical performance of the electrode.

[0036] 3. The present invention improves the mechanical strength of the electrode through the porous structure of the sandwich structure and covalent bond connection, prevents the active material from falling off, and extends the life of the electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 This is a scanning electron microscope image of the LIPG / LIPG@MnOx / LIPG composite material prepared in Example 1;

[0038] Figure 2 This is a scanning electron microscope cross-sectional image of the LIPG / LIPG@MnOx / LIPG composite material prepared in Example 1;

[0039] Figure 3 This is a transmission electron microscopy image of the LIPG / LIPG@MnOx / LIPG composite material prepared in Example 1;

[0040] Figure 4 X-ray photoelectron spectrum C1s of the LIPG / LIPG@MnOx / LIPG composite material prepared in Example 1;

[0041] Figure 5 X-ray photoelectron spectrum O1s of the LIPG / LIPG@MnOx / LIPG composite material prepared in Example 1;

[0042] Figure 6 X-ray photoelectron spectrum Mn2p of the LIPG / LIPG@MnOx / LIPG composite material prepared in Example 1;

[0043] Figure 7Raman spectra of the LIPG / LIPG@MnOx / LIPG composite material prepared in Example 1, the LIPG material prepared in Comparative Example 1, and the LIPG / LIPG@MnOx composite material prepared in Comparative Example 2;

[0044] Figure 8 X-ray diffraction patterns of the LIPG / LIPG@MnOx / LIPG composite material prepared in Example 1, the LIPG material prepared in Comparative Example 1, and the LIPG / LIPG@MnOx composite material prepared in Comparative Example 2;

[0045] Figure 9 CV curves of a three-electrode system assembled using the LIPG / LIPG@MnOx / LIPG composite material prepared in Example 1, the LIPG material prepared in Comparative Example 1, and the LIPG / LIPG@MnOx composite material prepared in Comparative Example 2 as working electrodes;

[0046] Figure 10 CP curves of a three-electrode system assembled using the LIPG / LIPG@MnOx / LIPG composite material prepared in Example 1, the LIPG material prepared in Comparative Example 1, and the LIPG / LIPG@MnOx composite material prepared in Comparative Example 2 as working electrodes;

[0047] Figure 11 The electrochemical cycling performance of a three-electrode system assembled using the LIPG / LIPG@MnOx / LIPG composite material prepared in Example 1, the LIPG material prepared in Comparative Example 1, and the LIPG / LIPG@MnOx composite material prepared in Comparative Example 2 as working electrodes;

[0048] Figure 12 CV curve of an asymmetric supercapacitor assembled with the LIPG / LIPG@MnOx / LIPG composite material prepared in Example 1 as the positive electrode;

[0049] Figure 13 The electrochemical cycling performance of an asymmetric supercapacitor assembled with the LIPG / LIPG@MnOx / LIPG composite material prepared in Example 1 as the positive electrode;

[0050] Figure 14 This is the Raman spectrum of the LIPG / LIPG@FeOx / LIPG composite material prepared in Example 2;

[0051] Figure 15 This is the Raman spectrum of the LIPG / LIPG@NiOx / LIPG composite material prepared in Example 3;

[0052] Figure 16This is the Raman spectrum of the LIPG / LIPG@CoOx / LIPG composite material prepared in Example 4. DETAILED DESCRIPTION

[0053] In order to make the technical means, creative features, objectives and effects achieved by the present invention easier to understand, the present invention is further described below with reference to specific embodiments and illustrations.

[0054] Reagents and equipment:

[0055] Phenolic resin (PR) powder was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0056] Polyimide (PI) powder was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0057] Polyethylene terephthalate (PET) substrate, 60 μm thick film, was purchased from Ruixin Plastic Industry Co., Ltd.

[0058] PI substrate, a film with a thickness of 50 μm, was purchased from Jinfuchen (Dongguan) New Material Technology Co., Ltd.

[0059] Commercial activated carbon AC was purchased from Changzhou Zhongtan New Material Technology Co., Ltd.

[0060] CO2 laser, model Han's Laser D200, was purchased from Han's Laser Technology Industry Group Co., Ltd.

[0061] Example 1

[0062] 1. Preparation of LIPG / LIPG@MnOx / LIPG

[0063] (1) 6 g of PR powder was added to 17.5 mL of anhydrous ethanol, stirred evenly, dried at 85 °C for 2 h to remove part of the solvent, and ultrasonicated for 30 min to remove bubbles. The solution was then evenly coated on a PET substrate and air-dried to obtain a PR film.

[0064] (2) The PR film was irradiated with CO2 laser under the conditions of laser wavelength of 10.6 μm, laser power of 6.0 W, scanning spacing of 0.1 mm, scanning rate of 20 mm / s, spot size of 50 μm, pulse frequency of 5 kHz, focal length of 575 mm, and voltage of 220 V to form the first LIPG layer.

[0065] (3) A mixed solution of manganese acetate, PR powder, and anhydrous ethanol was evenly coated on the surface of the first LIPG layer, wherein the concentration of manganese acetate was 0.4 mol / L and the mass ratio of PR powder to manganese acetate was 2:1. ,The coating thickness is 300 μm. After standing for 30 minutes, it is placed in an 80°C oven for annealing for 1 hour. Subsequently, CO2 laser irradiation is carried out under the conditions of laser wavelength 10.6 μm, laser power 7.0 W, scanning spacing 0.1 mm, scanning rate 20 mm / s, spot size 50 μm, pulse frequency 5 kHz, focal length 575 mm, and voltage 220 V to form a LIPG@MnOx composite layer.

[0066] (4) A PR solution (prepared from PR powder and anhydrous ethanol) with a concentration of 0.343 g / mL was evenly coated on the surface of the LIPG@MnOx composite layer. After standing for 30 min, it was placed in an 80°C oven for annealing for 1 h. Then, CO2 laser irradiation was performed under the conditions of laser wavelength 10.6 μm, laser power 6.0 W, scanning spacing 0.1 mm, scanning rate 20 mm / s, spot size 50 μm, pulse frequency 5 kHz, focal length 575 mm, and voltage 220 V to form a second LIPG layer. Finally, it was immersed in anhydrous ethanol for 3 h to peel off the PET substrate to obtain a sandwich structure composite material (LIPG / LIPG@MnOx / LIPG).

[0067] from Figure 1 It can be seen that manganese oxide is loaded on LIPG.

[0068] from Figure 2 It can be seen that the cross-section of the sandwich structure composite material has a three-layer structure.

[0069] from Figure 3 It can be seen that the morphology of manganese oxides in the sandwich structure composite material includes Mn2O3 and MnO2.

[0070] from Figure 4-6 It can be seen that the element content and existence form of each element C, O, and Mn in the sandwich structure composite material.

[0071] from Figure 7-8 It can be seen that LIPG is of good quality and its material composition is LIPG, Mn2O3 and MnO2.

[0072] 2. Assembly of three-electrode system and its electrochemical performance testing

[0073] The LIPG / LIPG@MnOx / LIPG prepared in Example 1 was cut into 1cm×1cm size and used as the working electrode. A platinum sheet was used as the counter electrode, silver chloride was used as the reference electrode, and 1 mol / L sulfuric acid solution was used as the electrolyte. The electrochemical performance test was carried out using a three-electrode system. The test results showed that at 5.0 mA / cm 2 At a high current density, the specific capacitance of the three electrodes reaches 225.0mF / cm 2 ; at 1.0 mA / cm 2At a current density of 1.5 GHz, the specific capacitance of the three electrodes reaches 1940.3 mF / cm 2 ; After 5000 cycles, the capacitance retention rate is 92.07%.

[0074] As can be seen from Figures 9-11, compared with LIPG and LIPG / LIPG@MnOx, the electrochemical performance of the LIPG / LIPG@MnOx / LIPG composite material of the present invention as an electrode is better.

[0075] 3. Assembly of asymmetric supercapacitors and their electrochemical performance testing

[0076] Commercial activated carbon (AC), acetylene black, and polyvinylidene fluoride (PVDF) were dispersed in N-methylpyrrolidone at a weight ratio of 8:1:1 and stirred to form a uniform slurry. The slurry was then evenly coated onto copper foil to a thickness of 15 μm on one side and 30 μm on both sides. The resulting slurry was vacuum-dried at 60°C and naturally cooled to room temperature to obtain a negative electrode. The LIPG / LIPG@MnOx / LIPG prepared in Example 1 was used as the positive electrode. Both the positive and negative electrodes were 2 cm × 1 cm in size. A 1 mol / L sulfuric acid solution was used as the electrolyte to assemble an asymmetric supercapacitor.

[0077] from Figure 12 and 13 It can be seen that the assembled asymmetric supercapacitor achieves a wide potential window of 0-1.6 V and significantly improves the energy density (199 μWh / cm 2 ) and power density (600μW / cm 2 ), and it can still retain 94% of the capacitance retention after 10,000 cycles.

[0078] Example 2

[0079] Preparation of LIPG / LIPG@FeOx / LIPG

[0080] (1) 6 g of PI powder was added to 25 mL of anhydrous ethanol, stirred evenly, dried at 85 °C for 2 h to remove part of the solvent, and ultrasonicated for 20 min to remove bubbles. The solution was then evenly coated on a PET substrate and air-dried to obtain a PI film.

[0081] (2) The PI film was irradiated with CO2 laser under the conditions of laser wavelength of 10.6 μm, laser power of 6.0 W, scanning spacing of 0.2 mm, scanning rate of 20 mm / s, spot size of 50 μm, pulse frequency of 5 kHz, focal length of 575 mm, and voltage of 220 V to form the first LIPG layer.

[0082] (3) A mixed solution of ferric acetate, PI powder, and anhydrous ethanol was evenly coated on the surface of the first LIPG layer, wherein the concentration of ferric acetate was 0.4 mol / L and the mass ratio of PI powder to ferric acetate was 2:1. , The coating thickness is 400μm. After standing for 30min, it is placed in an 80℃ oven for annealing for 1h. Then, CO2 laser irradiation is performed under the conditions of laser wavelength 10.6μm, laser power 7.0W, scanning spacing 0.2mm, scanning rate 20mm / s, spot size 50μm, pulse frequency 5kHz, focal length 575mm, and voltage 220V to form a LIPG@FeOx composite layer. Figure 1 It can be seen that iron oxides are loaded on LIPG.

[0083] (4) A PI solution with a concentration of 0.382 g / mL (prepared by PI powder and anhydrous ethanol) was evenly coated on the surface of the LIPG@FeOx composite layer. After standing for 30 min, it was placed in an 80°C oven for annealing for 1 h. Then, CO2 laser irradiation was performed under the conditions of laser wavelength 10.6 μm, laser power 6.0 W, scanning spacing 0.2 mm, scanning rate 20 mm / s, spot size 50 μm, pulse frequency 5 kHz, focal length 575 mm, and voltage 220 V to form a second LIPG layer. Finally, it was immersed in anhydrous ethanol for 4 h to peel off the PET substrate to obtain a sandwich structure composite material (LIPG / LIPG@FeOx / LIPG).

[0084] from Figure 14 It can be seen that the forms of iron oxides are mainly Fe3O4 and Fe2O3.

[0085] Example 3

[0086] Preparation of LIPG / LIPG@NiOx / LIPG

[0087] (1) 6 g of PR powder was added to 17.5 mL of anhydrous ethanol, stirred evenly, dried at 85 °C for 2 h to remove part of the solvent, and ultrasonicated for 30 min to remove bubbles. The solution was then evenly coated on a PI substrate and air-dried to obtain a PR film.

[0088] (2) The PR film was irradiated with CO2 laser under the conditions of laser wavelength of 10.6 μm, laser power of 8.0 W, scanning spacing of 0.1 mm, scanning rate of 30 mm / s, spot size of 50 μm, pulse frequency of 5 kHz, focal length of 575 mm, and voltage of 220 V to form the first LIPG layer.

[0089] (3) A mixed solution of nickel acetate, PR powder, and anhydrous ethanol was uniformly coated on the surface of the first LIPG layer, wherein the concentration of nickel acetate was 0.4 mol / L, and the mass ratio of PR powder to manganese acetate was 2:1., The coating thickness is 300 μm. After standing for 30 minutes, it is placed in an 80°C oven for annealing for 1 hour. Subsequently, CO2 laser irradiation is carried out under the conditions of laser wavelength 10.6 μm, laser power 7.0 W, scanning spacing 0.1 mm, scanning rate 30 mm / s, spot size 50 μm, pulse frequency 10 kHz, focal length 575 mm, and voltage 220 V to form a LIPG@NiOx composite layer.

[0090] (4) A PR solution (prepared from PR powder and anhydrous ethanol) with a concentration of 0.318 g / mL was evenly coated on the surface of the LIPG@NiOx composite layer. After standing for 30 min, it was placed in an 80°C oven for annealing for 1 h. Then, CO2 laser irradiation was performed under the conditions of laser wavelength 10.6 μm, laser power 8.0 W, scanning spacing 0.1 mm, scanning rate 30 mm / s, spot size 50 μm, pulse frequency 5 kHz, focal length 575 mm, and voltage 220 V to form a second LIPG layer. Finally, it was immersed in anhydrous ethanol for 3 h to peel off the PI substrate to obtain a sandwich structure composite material (LIPG / LIPG@NiOx). x / LIPG).

[0091] from Figure 15 It can be seen that the morphology of nickel oxide is mainly NiO.

[0092] Example 4

[0093] Preparation of LIPG / LIPG@CoOx / LIPG

[0094] (1) 5 g of PR powder was added to 15 mL of anhydrous ethanol, stirred evenly, dried at 85 °C for 2 h to remove part of the solvent, and ultrasonicated for 30 min to remove bubbles. The solution was then evenly coated on a PET substrate and air-dried to obtain a PR film.

[0095] (2) The PR film was irradiated with CO2 laser under the conditions of laser wavelength of 10.6 μm, laser power of 6.0 W, scanning spacing of 0.2 mm, scanning rate of 20 mm / s, spot size of 100 μm, pulse frequency of 5 kHz, focal length of 575 mm, and voltage of 220 V to form the first LIPG layer.

[0096] (3) A mixed solution of cobalt acetate, PR powder, and anhydrous ethanol was evenly coated on the surface of the first LIPG layer, wherein the concentration of cobalt acetate was 0.5 mol / L and the mass ratio of PR powder to cobalt acetate was 2:1. ,The coating thickness is 300 μm. After standing for 30 minutes, it is placed in an 80°C oven for annealing for 1 hour. Subsequently, CO2 laser irradiation is carried out under the conditions of laser wavelength 10.6 μm, laser power 7.0 W, scanning spacing 0.2 mm, scanning rate 20 mm / s, spot size 100 μm, pulse frequency 5 kHz, focal length 575 mm, and voltage 220 V to form a LIPG@CoOx composite layer.

[0097] (4) A PR solution (prepared from PR powder and anhydrous ethanol) with a concentration of 0.343 g / mL was evenly coated on the surface of the LIPG@CoOx composite layer. After standing for 30 min, it was placed in an 80°C oven for annealing for 1 h. Then, CO2 laser irradiation was performed under the conditions of laser wavelength 10.6 μm, laser power 7.0 W, scanning spacing 0.2 mm, scanning rate 20 mm / s, spot size 100 μm, pulse frequency 5 kHz, focal length 575 mm, and voltage 220 V to form a second LIPG layer. Finally, it was immersed in anhydrous ethanol for 4 h to peel off the PET substrate to obtain a sandwich structure composite material (LIPG / LIPG@CoO x / LIPG).

[0098] from Figure 16 It can be seen that the forms of cobalt oxides are mainly Co3O4 and CoO.

[0099] Comparative Example 1

[0100] Preparation of LIPG materials

[0101] LIPG material was prepared according to steps (1) and (2) of Example 1, and the electrochemical performance test was carried out using the three-electrode system of Example 1. The test results showed that at 5.0 mA / cm 2 At a high current density, the specific capacitance of the three electrodes is only 20.1mF / cm 2 ; at 1.0 mA / cm 2 At a current density of 1.5, the specific capacitance of the three electrodes is 119 mF / cm 2 , after 5000 cycles, the capacitance retention rate is 92.59%.

[0102] Comparative Example 2

[0103] Preparation of LIPG / LIPG@MnOx composite materials

[0104] The LIPG / LIPG@MnOx composite material was prepared according to steps (1) to (3) of Example 1, and the electrochemical performance test was carried out using the three-electrode system of Example 1. The test results showed that at 5.0 mA / cm 2 At high current density, the specific capacitance is 120.1mF / cm 2 ; at 1.0 mA / cm2 At a current density of 1.5, the specific capacitance is 1251.5mF / cm 2 , after 5000 cycles, the capacitance retention rate is 85.97%.

[0105] Comparing Example 1 with Comparative Examples 1 and 2, it can be seen that:

[0106] 1. Although the conventional single-layer LPG electrode (Comparative Example 1) has good conductivity, its specific capacitance is low, only 20.1 mF / cm, due to the lack of pseudocapacitive active materials. 2 , and the cyclic stability is poor.

[0107] 2. Although the pseudocapacitive active material MnOx was introduced into the LPG / LPG@MnOx double-layer electrode (Comparative Example 2), the specific capacitance was improved, but it was still lower than that of the sandwich structure electrode, and the cycle stability was not significantly improved.

[0108] 3. The sandwich structure composite electrode of the present invention (Example 1) has a unique structural design, which makes full use of the high conductivity and porosity of the LPG layer and the pseudocapacitive activity of MnOx to achieve a significant improvement in specific capacitance (1940.3mF / cm 2 ), and maintained a capacitance retention rate of 92.07% after 10,000 cycles, demonstrating excellent cycling stability. Furthermore, the sandwich structure design effectively prevents the shedding of MnOx during cycling, further extending the life of the electrode.

[0109] In summary, the sandwich structure composite electrode of the present invention is superior to the traditional single-layer LPG electrode and double-layer LPG / LPG@MnOx electrode in terms of electrochemical performance and cycle stability, and has significant innovation and practicality.

[0110] The basic principles, main features, and advantages of the present invention are shown and described above. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are merely illustrative of the principles of the present invention. Various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention. Such changes and modifications are intended to fall within the scope of the present invention. The scope of protection claimed in the present invention is defined by the appended claims and their equivalents.

Claims

1. A sandwich structure composite material, characterized by: The invention comprises a first LIPG layer, a LIPG@pseudocapacitive material composite layer and a second LIPG layer, wherein the LIPG@pseudocapacitive material composite layer is arranged between the first LIPG layer and the second LIPG layer.

2. The sandwich structure composite material according to claim 1, characterized in that: The pseudocapacitive material is a transition metal oxide selected from one or more of manganese oxide, iron oxide, cobalt oxide, and nickel oxide; Preferably, the pseudocapacitive material is a heterostructure of Mn3O4 and MnO2.

3. The sandwich structure composite material according to claim 1, characterized in that: The thickness of the first LIPG layer and the second LIPG layer are both 150-200 μm; the pore size distribution of the first LIPG layer and the second LIPG layer is small mesopores of 2-5 nm; Preferably, the thickness of the LIPG@pseudocapacitive material layer is 200-300 μm; the pore size distribution of the LIPG@pseudocapacitive material layer is macromesopores of 5-50 nm; Preferably, the specific surface area of ​​the first LIPG layer and the second LIPG layer is 500-600 m2 / g, and the conductivity is 800-1000 S / m; Preferably, the mass proportion of the pseudocapacitive material in the LIPG@pseudocapacitive material layer is 10-20%.

4. The method for preparing the sandwich structure composite material according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) forming a carbon precursor into a thin film and irradiating it with a laser to form a first LIPG layer; (2) uniformly coating a mixed solution of a carbon precursor and a pseudocapacitive material precursor on the surface of the first LIPG layer, and irradiating the layer with a laser to form a LIPG@pseudocapacitive material composite layer on the first LIPG layer; (3) A carbon precursor solution is uniformly coated on the surface of the LIPG@pseudocapacitor material composite layer, and laser irradiation is performed to form a second LIPG layer on the LIPG@pseudocapacitor material composite layer to obtain a sandwich structure composite electrode material.

5. The preparation method according to claim 4, characterized in that: The carbon precursor is selected from one or more of polymers, lignin, cellulose, activated carbon, biomass carbon, graphite, coke, and pyrolytic carbon; Preferably, the pseudocapacitive material precursor is a transition metal salt selected from one or more of manganese acetate, iron acetate, nickel acetate, and cobalt acetate; Preferably, the substrate is made of one or more of polymer, metal, carbon, and carbon fiber; Preferably, the substrate is in the form of one or more of film, powder, fiber, paper, cloth, and foam; Preferably, the mass ratio of the carbon precursor to the pseudocapacitive material precursor in the mixed solution is 1.5-2.5:

1.

6. The preparation method according to claim 4, wherein: The laser is one or more of solid laser, liquid laser, gas laser, semiconductor laser, fiber laser, pulse laser, and continuous wave laser; Preferably, the laser wavelength of the laser irradiation is 1-1000 μm, the laser power is 0.1-100 W, the scanning rate is 1-2000 mm / s, and the spot size is 10 -9 ~10 2 m, scanning spacing is 0.01~5mm, pulse frequency is 1~100kHz, focal length is 1~200cm, voltage is 0.01~1000kV; Preferably, an annealing treatment is added before laser irradiation is performed on the first LIPG layer coated with a mixed solution of a carbon precursor and a pseudocapacitive material precursor and the LIPG@pseudocapacitive material composite layer coated with a carbon precursor solution; Preferably, the annealing treatment is performed at a temperature of 60 to 80° C. and for a time of 0.8 to 1 h.

7. Use of the sandwich structure composite material according to any one of claims 1 to 3 or the sandwich structure composite material prepared by the preparation method according to any one of claims 4 to 6 in supercapacitors.

8. A supercapacitor, characterized in that: The sandwich structure composite material according to any one of claims 1 to 3 or the sandwich structure composite material prepared by the preparation method according to any one of claims 4 to 6 is used as the positive electrode and / or the negative electrode.

9. An asymmetric supercapacitor, characterized in that: The sandwich structure composite material according to any one of claims 1 to 3 or the sandwich structure composite material prepared by the preparation method according to any one of claims 4 to 6 is used as the positive electrode.

10. The asymmetric supercapacitor according to claim 9, characterized in that: The asymmetric supercapacitor has a potential window of 0-1.6 V and an energy density of 190-200 μWh·cm -2 , power density is 500~600μW·cm -2 , the capacitance retention rate is greater than 90% after 10,000 cycles.